Analisis Laporan Keuangan Dalam Menilai Kinerja Keuangan Industri Semen Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Dharma, Budi; Nafis, Fadly Abdillah; Fadillah, Aditya (Universitas Labuhanbatu, 2022)
It is important for businesses to conduct financial performance appraisals, used to measure and evaluate financial status in general. The method used to analyze the company's financial statements is a measurement method through the ratios of liquidity, solvency and profitability used to determine the company's financial position. As well as being part of the method of assessing finances used in the balance sheet analysis method. The data used to assess performance comes from the company's financial statements that will be examined, namely PT Indocement Tunggal Prakarsa Tbk from 2010 to 2014 which will be evaluated through several ratios that will be utilized. Based on the results obtained through the discussion, the financial results of PT Indocement Tunggal Prakarsa Tbk fluctuate every year due to changes in balance sheet items such as sales, inventories, profits, and others.